The first voltammetric investigation for astilbin based on β-cyclodextrin functionalized graphene modified electrode. Issue 24 (3rd June 2016) - Wang, Lu; Wang, Qinqin; Sheng, Kai; Zou, Lina; Ye, Baoxian
Abstract : The electrochemical properties of astilbin were investigated for the first time and an electroanalytical method was established synchronously, which was based on a β-cyclodextrin–graphene nanocomposite modified electrode. Abstract : In this study, the electrochemical properties of astilbin were investigated for the first time and an electroanalytical method was established synchronously, which was based on a β-cyclodextrin–graphene nanocomposite modified electrode (β-CD–GNs/GCE). The electrode process of astilbin was investigated in detail, and some dynamic parameters were calculated. The detecting sensitivity of astilbin was greatly enhanced at this voltammetric sensor. Under optimum conditions, a lower detection limit (1 × 10 −8 mol L −1 ) and wider linear range (3.0 × 10 −8 mol L −1 to 2.0 × 10 −6 mol L −1 ) were achieved by the proposed sensor. Finally, the proposed method was applied to the analysis of a real sample, and the results showed that the method was applicable and reliable.